2023
DOI: 10.1186/s13071-022-05641-9
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide host associations of the tick genus Ixodes suggest relationships based on environmental sharing rather than on co-phylogenetic events

Abstract: Background This study aims to capture how ticks of the genus Ixodes gained their hosts using network constructs. We propose two alternative hypotheses, namely, an ecological background (ticks and hosts sharing environmentally available conditions) and a phylogenetic one, in which both partners co-evolved, adapting to existing environmental conditions after the association took place. Methods We used network constructs linking all the known pairs of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 55 publications
1
1
0
Order By: Relevance
“…The tick vectors could be environmentally associated with the vertebrates, while the microorganism could have true phylogenetic associations with the vertebrates. Similar associations were recognized for the genus Ixodes in the Neotropics ( Estrada-Peña et al, 2023 ). A deeper approach to the evolutionary background of Borrelia ( OʼKeeffe et al, 2020 ) suggested that the distribution of Borrelia and its genetic structure is shaped by the contact with key vertebrates.…”
Section: Introductionsupporting
confidence: 77%
“…The tick vectors could be environmentally associated with the vertebrates, while the microorganism could have true phylogenetic associations with the vertebrates. Similar associations were recognized for the genus Ixodes in the Neotropics ( Estrada-Peña et al, 2023 ). A deeper approach to the evolutionary background of Borrelia ( OʼKeeffe et al, 2020 ) suggested that the distribution of Borrelia and its genetic structure is shaped by the contact with key vertebrates.…”
Section: Introductionsupporting
confidence: 77%
“…of vector population dynamics and their interactions with the environment seems essential to surveillance vector-borne diseases [5,6,7]. The most important factor is climate change [8,9].…”
mentioning
confidence: 99%